High entropy fine particle size vacancy-rich hexacyanoferrate and preparation method and application thereof

Through the preparation of high-entropy fine particle size vacanoferrate, combined with grain refinement and high-entropy strategies, the problems of poor conductivity and structural deterioration of hexacyanoferrate in aqueous metal ion batteries are solved. It achieves high specific capacity, good rate performance and long cycle life, and shows compatibility in a variety of electrochemical systems, promoting the commercial application of water-based batteries.

CN119008937BActive Publication Date: 2025-01-07SANYA SCI & EDUCATION INNOVATION PARK WUHAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411498968.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-07
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The existing hexacyanoferrate positive electrode material in water-based metal ion batteries has poor intrinsic conductivity, structural deterioration, and the dissolution of transition metal ions and ferrocyanogenic roots during the cycle, resulting in poor rate performance and short cycles. Lifespan and difficult to show compatibility and excellent electrochemical properties in a variety of electrochemical systems.

Method used

By preparing high-entropy fine particle size vacanciferate, the chemical formula is KxM[Fe(CN)6]y•zH2O, combined with grain refinement, introduction of vacancy and high-entropy strategies, the transition metal element is Fe, Co, Ni, Cu and Mn, particle sizes of 15~25nm, vacancian ions and potassium ions are introduced, and specific precipitation methods and process conditions are used to optimize the structure and performance of the material.

Benefits of technology

Achieve high specific capacity, good rate performance and excellent cycle stability, and show strong compatibility and excellent electrochemical performance in various water-based metal ion batteries, simplifying the synthesis process, reducing energy consumption and cost, and promoting The commercialization process of water-based metal ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119008937B_ABST
    Figure CN119008937B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemical devices and discloses a high-entropy fine-particle vacancy-rich hexacyanoferrate having a chemical formula of K x M[Fe(CN) 6 ] y • 2 O, where M is a transition metal element, 0.75≤x≤1, 0.4≤y≤0.6, z≤4.0, there are five transition metal elements, the molar mass of each transition metal element accounts for 20%~30% of all transition metal elements, the molar mass of vacancies in ferrocyanide ions accounts for 30%~50%, and the molar mass of vacancies in K ions accounts for 30%~60%. The present invention also discloses a preparation method of the high-entropy, fine-particle-size, vacancy-rich hexacyanoferrate and its application in aqueous metal ion batteries. The present invention endows the hexacyanoferrate material with high specific capacity, excellent rate performance and good cycle stability in a variety of aqueous metal ion batteries through particle size refinement and vacancy-rich design.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochemical devices, and in particular to a high-entropy fine-particle vacancy-rich hexacyanoferrate and a preparation method and application thereof. Background Art

[0002] Large-scale energy storage technology is essential for the efficient use of renewable energy. Aqueous metal-ion batteries have great commercial prospects because of their safety, environmental friendliness, low cost, high energy density and high power density. However, aqueous electrolytes face problems such as metal ion solvation and water dissociation, which makes the energy storage mechanism of positive electrode materials more complex. At the same time, the strong interaction between hydrated metal ions and host materials makes it difficult to reversibly embed / eject. Therefore, the development of efficient electrode materials is crucial for aqueous metal-ion battery systems.

[0003] Prussian blue analogs have been widely studied due to their open three-dimensional framework structure, which can provide a fast ion deintercalation environment. Among the many Prussian blue analogs, hexacyanoferrate stands out because of its high theoretical energy density and ability to perform double electron transfer, but it still faces the problems of poor intrinsic conductivity and structural degradation caused by the dissolution of transition metal ions and ferrocyanide during the cycle, thus showing poor rate performance and short cycle life. Although researchers have proposed a variety of optimization strategies (morphology design, heterogeneous element doping, material composite, etc.), the improvement effect still has certain limitations, especially when facing a variety of aqueous metal ion batteries, showing poor compatibility, and the electrochemical performance is often only optimized in one or a few systems, which cannot achieve the material requirements faced by a single material for multiple electrochemical systems and large-scale energy storage applications. Therefore, it is of great significance to optimize the intrinsic structure of the material and then realize the application of a single cathode material in multiple electrochemical systems for its commercial application.

[0004] Grain refinement, introduction of vacancies, and high entropy treatment are effective strategies for optimizing intrinsic structures, and have become a consensus in the scientific research community. However, grain refinement often requires increased crystallinity, and the introduction of vacancies will reduce crystallinity and destroy structural stability. The charge compensation mechanism introduced by high entropy treatment limits the generation of vacancies, and the three factors restrict each other and are difficult to coordinate and regulate. Summary of the invention

[0005] The purpose of the present invention is to address the deficiencies of the above-mentioned technologies and provide a high-entropy, fine-particle, vacancy-rich hexacyanoferrate and its preparation method and application, so as to achieve particle size refinement and vacancy enrichment of high-entropy hexacyanoferrate, and exhibit high specific capacity, good rate and cycle performance in a variety of aqueous metal ion batteries.

[0006] In order to achieve the above-mentioned purpose, the present invention designs a high entropy fine particle size vacancy-rich hexacyanoferrate, the chemical formula of which is K x M[Fe(CN)6]y •zH2O, where M is a transition metal element, 0.75≤x≤1, 0.4≤y≤0.6, z≤4.0, there are five transition metal elements, and the molar mass of each transition metal element accounts for 20%~30% of all transition metal elements, the molar mass of the vacancy in the ferrocyanide ion accounts for 30%~50%, and the molar mass of the vacancy in the K ion accounts for 30%~60%.

[0007] Preferably, the particle size is 15 to 25 nm.

[0008] Preferably, the transition metal elements include Fe, Co, Ni, Cu and Mn.

[0009] Preferably, the molar masses of the transition metal elements are the same.

[0010] A method for preparing high-entropy fine-particle vacancy-rich hexacyanoferrate comprises the following steps:

[0011] A) dissolving the transition metal element salt and the chelating agent in deionized water, stirring to completely dissolve and mix evenly to obtain a clear and transparent solution;

[0012] B) dissolving potassium ferrocyanide and the chelating agent in deionized water, stirring to completely dissolve and mix evenly to obtain a clear and transparent solution II;

[0013] C) Under an inert gas atmosphere, solution 1 and solution 2 were quickly transferred to a constant pressure dropping funnel, and were slowly dripped into deionized water using a peristaltic pump while continuously stirring to obtain solution 3;

[0014] D) aging solution three at room temperature;

[0015] E) The precipitate was collected by centrifugation, and the obtained product was washed with deionized water and ethanol, and then dried in a vacuum oven.

[0016] Preferably, the anion of the transition metal element salt is Cl2²¯ or SO4²¯.

[0017] Preferably, in the step A), the chelating agent is Na3C6H5O7·2H2O, the molar amount of the chelating agent is one fifth of the total molar amount of the transition metal element in the transition metal element salt, and the stirring time is 0.5 to 1 h. In the step B), the molar amount of the chelating agent is the same as the molar amount of the chelating agent in the step A), the molar amount of potassium ferrocyanide is 6 times the molar amount of the chelating agent, and the stirring time is 0.5 to 1 h.

[0018] Preferably, in step C), the inert gas is N2, the dripping rate of solution 1 and solution 2 is 15-25 ml / h, and stirring is continued at 600 rpm for 2-3 h.

[0019] Preferably, in step D), the aging time is 20 to 30 hours, and in step E), the mixture is washed with deionized water 3 times and with ethanol once, each time for 5 minutes, and dried in a vacuum oven at 110 to 150° C. for 20 to 30 hours.

[0020] The invention discloses an application of high entropy fine-particle vacancy-rich hexacyanoferrate for positive electrode materials of aqueous metal ion batteries.

[0021] The principle of the present invention is: to optimize the intrinsic structure of hexacyanoferrate positive electrode materials, to improve the electron conduction and ion diffusion rate of the positive electrode by introducing vacancies, to shorten the ion migration distance by particle size refinement, and to optimize the cycle stability of hexacyanoferrate positive electrode materials by high entropy. This preparation method combines three strategies (grain refinement, introduction of vacancies, and high entropy) for the first time. Transition metal element salts and potassium ferrocyanide are co-precipitated under an inert atmosphere at room temperature. The particle size and the number of defects are assisted in adjusting the reaction rate by changing the reaction rate with citrate and sodium ions, thereby constructing a hexacyanoferrate positive electrode material with fine particle size (15-25nm), rich vacancies (molar ratio ≥30%), and high entropy effect, which synergistically improves the electrochemical performance of hexacyanoferrate, and verifies its universality in multi-system aqueous metal ion batteries.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] 1. The prepared high-entropy, fine-particle, vacancy-rich hexacyanoferrate was used as the positive electrode material for aqueous metal ion batteries for electrochemical performance testing, showing strong compatibility, high specific capacity, good rate and cycle performance;

[0024] 2. The intrinsic optimization strategy of synergistic grain refinement, introduction of vacancies, and high entropy can stably synthesize a new high-entropy hexacyanoferrate cathode material with a particle size of 15-25 nm and rich in ferrocyanide and potassium ion vacancies;

[0025] 3. The synthesis process is simple, with low energy consumption and cost, which is conducive to promoting the commercialization of aqueous metal ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The XRD diagrams of the high entropy fine-particle vacancy-rich hexacyanoferrate positive electrode material prepared in Example 1 of the present invention and potassium manganese hexacyanoferrate in Comparative Example 1;

[0027] Figure 2 The ICP data of the high entropy fine-particle vacancy-rich hexacyanoferrate positive electrode material prepared in Example 1 of the present invention and potassium manganese hexacyanoferrate in Comparative Example 1;

[0028] Figure 3 The TG data of the high entropy fine-particle vacancy-rich hexacyanoferrate positive electrode material prepared in Example 1 of the present invention and potassium manganese hexacyanoferrate in Comparative Example 1;

[0029] Figure 4 This is a TEM image of the high entropy fine-grained vacancy-rich hexacyanoferrate positive electrode material prepared in Example 1 of the present invention;

[0030] Figure 5 It is an EPR graph of the high entropy fine-particle vacancy-rich hexacyanoferrate positive electrode material prepared in Example 1 of the present invention and potassium manganese hexacyanoferrate in Comparative Example 1;

[0031] Figure 6 CV diagram of the high entropy fine particle size vacancy-rich hexacyanoferrate cathode material prepared in Example 1 of the present invention and potassium manganese hexacyanoferrate in Comparative Example 1;

[0032] Figure 7 The high entropy fine-grained vacancy-rich hexacyanoferrate positive electrode material prepared in Example 1 of the present invention and the comparative example 1 are respectively assembled with carbon rods to form three electrodes, and the charge and discharge curves are compared at a current density of 50 mA / g;

[0033] Figure 8 The high entropy fine-grained vacancy-rich hexacyanoferrate positive electrode material prepared in Example 1 of the present invention and Comparative Example 1 are assembled with carbon rods to form three electrodes, and the capacity cycle comparison diagram at a current density of 50 mA / g;

[0034] Fig. 9 It is a comparison diagram of the rate cycle curves of the high entropy fine-particle vacancy-rich hexacyanoferrate positive electrode material prepared in Example 1 of the present invention and the comparative example 1 respectively assembled with carbon rods for three electrodes;

[0035] Fig.10 The high entropy fine-particle vacancy-rich hexacyanoferrate positive electrode material prepared in Example 1 of the present invention and the comparative example 1 are respectively assembled with carbon rods to form three electrodes, and the long cycle performance diagram at a current density of 1 A / g;

[0036] Fig.11 The high entropy fine-grained vacancy-rich hexacyanoferrate positive electrode material prepared in Example 1 of the present invention and the positive electrode material of Comparative Example 1 are respectively assembled with carbon rods to form three electrodes, and the rate cycle curve comparison diagram is measured when the electrolyte is 3M KCL and 3M KNO3;

[0037] Fig.12 The high-entropy, fine-particle, vacancy-rich hexacyanoferrate positive electrode material prepared in Example 1 of the present invention and the positive electrode material of Comparative Example 1 are respectively assembled with Zn metal into a buckle-cell full battery, and a comparison chart of the rate cycle curves measured when the electrolyte is 3M ZnSO4 and 3M Zn(OTF)2. DETAILED DESCRIPTION

[0038] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the technical solutions in the embodiments of the present invention will be clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.

[0039] A high entropy fine-particle vacancy-rich hexacyanoferrate with the chemical formula K x M[Fe(CN)6] y •zH2O, where M is a transition metal element, 0.75≤x≤1, 0.4≤y≤0.6, z≤4.0, there are five transition metal elements, and the molar mass of each transition metal element accounts for 15%~30% of all transition metal elements, the molar mass of the vacancy in the ferrocyanide ion accounts for 30%~50%, and the molar mass of the vacancy in the K ion accounts for 30%~60%.

[0040] Among them, the particle size is 15~25nm, the transition metal elements include Fe, Co, Ni, Cu and Mn, and the molar mass of the transition metal elements can be the same.

[0041] A method for preparing high-entropy fine-particle vacancy-rich hexacyanoferrate comprises the following steps:

[0042] A) dissolving the transition metal element salt and the chelating agent in deionized water, stirring to completely dissolve and mix evenly to obtain a clear and transparent solution;

[0043] B) dissolving potassium ferrocyanide and the chelating agent in deionized water, stirring to completely dissolve and mix evenly to obtain a clear and transparent solution II;

[0044] C) Under an inert gas atmosphere, solution 1 and solution 2 were quickly transferred to a constant pressure dropping funnel, and were slowly dripped into deionized water using a peristaltic pump while continuously stirring to obtain solution 3;

[0045] D) aging solution three at room temperature;

[0046] E) The precipitate was collected by centrifugation, and the obtained product was washed with deionized water and ethanol, and then dried in a vacuum oven.

[0047] Among them, the anion of the transition metal element salt is Cl2²¯ or SO4²¯.

[0048] In addition, in step A), the chelating agent is Na3C6H5O7·2H2O, the molar amount of the chelating agent is one-fifth of the total molar amount of the transition metal element in the transition metal element salt, and the stirring time is 0.5~1h. In the step B), the molar amount of the chelating agent is the same as the molar amount of the chelating agent in the step A), the molar amount of potassium ferrocyanide is 6 times the molar amount of the chelating agent, and the stirring time is 0.5~1h.

[0049] In step C), the inert gas is N2, the dripping rate of solution 1 and solution 2 is 15-25 ml / h, and stirring is continued at 600 rpm for 2-3 h.

[0050] In step D), the aging time is 20 to 30 hours. In step E), the product is washed with deionized water 3 times and ethanol once, each time for 5 minutes, and dried in a vacuum oven at 110 to 150° C. for 20 to 30 hours.

[0051] The high-entropy fine-particle vacancy-rich hexacyanoferrate of the invention is used as a positive electrode material for aqueous metal ion batteries. Example 1

[0052] A) Weigh transition metal salts: 0.4354 g manganese chloride (MnCl2·4H2O, relative molecular weight 197.91 g / mol, 2.2 mmol), 0.3976 g ferrous chloride (FeCl2·4H2O, relative molecular weight 198.81 g / mol, 2 mmol), 0.4759 g cobalt chloride (CoCl2·6H2O, relative molecular weight 237.93 g / mol, 2 mmol), 0.3410 g cupric chloride (CuCl2·2.5H2O, relative molecular weight 237.93 g / mol, 2 mmol), O, relative molecular weight of 179.49 g / mol, 1.9 mmol), 0.4516 g nickel chloride (NiCl2·6H2O, relative molecular weight of 237.69 g / mol, 1.9 mmol) and 0.5882 g chelating agent sodium citrate (Na3C6H5O7·2H2O, relative molecular weight of 294.10 g / mol, 2 mmol) were added to 50 ml deionized water, stirred to completely dissolve and mix evenly, and the stirring time was 1 hour to obtain a clear and transparent green solution 1;

[0053] B) Weigh 3.9509g potassium ferrocyanide (K3Fe(CN)6, relative molecular mass is 329.2443g / mol, 12mmol) and 0.5882g chelating agent sodium citrate (Na3C6H5O7·2H2O, relative molecular weight is 294.10g / mol, 2mmol) in 50ml deionized water, stir to completely dissolve and mix evenly, stirring time is 0.5h, to obtain a clear and transparent yellow solution II;

[0054] C) Take 100 ml of deionized water, and quickly transfer Solution 1 and Solution 2 to a constant pressure dropping funnel under a nitrogen atmosphere, and use a peristaltic pump to simultaneously drop deionized water at a rate of 20 ml / h to obtain Solution 3, and continue stirring Solution 3 for 3 hours at a speed of 600 rpm;

[0055] D) aging solution 3 at room temperature for 24 hours;

[0056] E) centrifugation, washing with deionized water for 3 times and ethanol for 1 time, each time at 10000 rpm for 5 min, and finally drying in a vacuum oven at 120 °C for 24 h to obtain high entropy, fine particle size, vacancy-rich hexacyanoferrate particles. Example 2

[0057] A) Weigh transition metal salts: 0.3958 g manganese chloride (MnCl2·4H2O, relative molecular weight 197.91 g / mol, 2 mmol), 0.3976 g ferrous chloride (FeCl2·4H2O, relative molecular weight 198.81 g / mol, 2 mmol), 0.4759 g cobalt chloride (CoCl2·6H2O, relative molecular weight 237.93 g / mol, 2 mmol), 0.3590 g cupric chloride (CuCl2·2.5H2O, relative molecular weight 237.93 g / mol, 2 mmol), O, relative molecular weight of 179.49 g / mol, 2 mmol), 0.4754 g nickel chloride (NiCl2·6H2O, relative molecular weight of 237.69 g / mol, 2 mmol) and 0.5882 g chelating agent sodium citrate (Na3C6H5O7·2H2O, relative molecular weight of 294.10 g / mol, 2 mmol) were added to 50 ml deionized water, stirred to completely dissolve and mix evenly, and the stirring time was 0.5 h to obtain a clear and transparent green solution 1;

[0058] B) Weigh 3.9509g potassium ferrocyanide (K3Fe(CN)6, relative molecular mass is 329.2443g / mol, 12mmol) and 0.5882g chelating agent sodium citrate (Na3C6H5O7·2H2O, relative molecular weight is 294.10g / mol, 2mmol) in 50ml deionized water, stir to completely dissolve and mix evenly, stirring time is 0.5h, to obtain a clear and transparent yellow solution II;

[0059] C) Take 100 ml of deionized water, and quickly transfer Solution 1 and Solution 2 to a constant pressure dropping funnel under a nitrogen atmosphere, and use a peristaltic pump to simultaneously drip into the deionized water at a rate of 15 ml / h to obtain Solution 3, and continue stirring Solution 3 for 2 hours at a speed of 600 rpm;

[0060] D) aging solution 3 at room temperature for 20 hours;

[0061] E) centrifugation, washing with deionized water for 3 times and ethanol for 1 time, each time at 10000 rpm for 5 min, and finally drying in a vacuum oven at 110 °C for 30 h to obtain high entropy, fine particle size, vacancy-rich hexacyanoferrate particles. Example 3

[0062] A) Weigh transition metal salts: 0.2969 g manganese chloride (MnCl2·4H2O, relative molecular weight 197.91 g / mol, 1.5 mmol), 0.2982 g ferrous chloride (FeCl2·4H2O, relative molecular weight 198.81 g / mol, 1.5 mmol), 0.7138 g cobalt chloride (CoCl2·6H2O, relative molecular weight 237.93 g / mol, 3 mmol), 0.3590 g cupric chloride (CuCl2·2.5 H2O, relative molecular weight of 179.49 g / mol, 2 mmol), 0.4754 g nickel chloride (NiCl2·6H2O, relative molecular weight of 237.69 g / mol, 2 mmol) and 0.5882 g chelating agent sodium citrate (Na3C6H5O7·2H2O, relative molecular weight of 294.10 g / mol, 2 mmol) were added to 50 ml deionized water, stirred to completely dissolve and mix evenly, and the stirring time was 0.6 h to obtain a clear and transparent green solution 1;

[0063] B) Weigh 3.9509g potassium ferrocyanide (K3Fe(CN)6, relative molecular mass is 329.2443g / mol, 12mmol) and 0.5882g chelating agent sodium citrate (Na3C6H5O7·2H2O, relative molecular weight is 294.10g / mol, 2mmol) in 50ml deionized water, stir to completely dissolve and mix evenly, stirring time is 0.5h, to obtain a clear and transparent yellow solution II;

[0064] C) Take 100 ml of deionized water, and quickly transfer Solution 1 and Solution 2 to a constant pressure dropping funnel under a nitrogen atmosphere, and use a peristaltic pump to simultaneously drop deionized water at a rate of 25 ml / h to obtain Solution 3, and continue stirring Solution 3 for 3 hours at a speed of 600 rpm;

[0065] D) aging solution 3 at room temperature for 24 hours;

[0066] E) centrifugation, washing with deionized water for 3 times and ethanol for 1 time, each time at 10000 rpm for 5 min, and finally drying in a vacuum oven at 150 °C for 20 h to obtain high entropy, fine particle size, vacancy-rich hexacyanoferrate particles. Example 4

[0067] A) Weigh transition metal salts: 0.5937 g manganese chloride (MnCl2·4H2O, relative molecular weight 197.91 g / mol, 3 mmol), 0.3976 g ferrous chloride (FeCl2·4H2O, relative molecular weight 198.81 g / mol, 2 mmol), 0.3569 g cobalt chloride (CoCl2·6H2O, relative molecular weight 237.93 g / mol, 1.5 mmol), 0.2692 g cupric chloride (CuCl2·2.5H2O, relative molecular weight 237.93 g / mol, 1.5 mmol), O, relative molecular weight of 179.49 g / mol, 1.5 mmol), 0.4754 g nickel chloride (NiCl2·6H2O, relative molecular weight of 237.69 g / mol, 2 mmol) and 0.5882 g chelating agent sodium citrate (Na3C6H5O7·2H2O, relative molecular weight of 294.10 g / mol, 2 mmol) were added to 50 ml deionized water, stirred to completely dissolve and mix evenly, and the stirring time was 0.8 h to obtain a clear and transparent green solution 1;

[0068] B) Weigh 3.9509g potassium ferrocyanide (K3Fe(CN)6, relative molecular mass is 329.2443g / mol, 12mmol) and 0.5882g chelating agent sodium citrate (Na3C6H5O7·2H2O, relative molecular weight is 294.10g / mol, 2mmol) in 50ml deionized water, stir to completely dissolve and mix evenly, stirring time is 0.5h, to obtain a clear and transparent yellow solution II;

[0069] C) Take 100 ml of deionized water, and quickly transfer Solution 1 and Solution 2 to a constant pressure dropping funnel under a nitrogen atmosphere, and use a peristaltic pump to simultaneously drop deionized water at a rate of 20 ml / h to obtain Solution 3, and continue stirring Solution 3 for 3 hours at a speed of 600 rpm;

[0070] D) aging solution 3 at room temperature for 30 hours;

[0071] E) centrifugation, washing with deionized water for 3 times and ethanol for 1 time, each time at 10000 rpm for 5 min, and finally drying in a vacuum oven at 120 °C for 24 h to obtain high entropy, fine particle size, vacancy-rich hexacyanoferrate particles. Example 5

[0072] A) Weigh transition metal salts: 0.4460 g manganese sulfate monohydrate (MnSO4·H2O, relative molecular weight 223 g / mol, 2 mmol), 0.8342 g ferrous sulfate heptahydrate (FeSO4·7H2O, relative molecular weight 278.05 g / mol, 3 mmol), 0.5622 g cobalt sulfate heptahydrate (CoSO4·7H2O, relative molecular weight 281.103 g / mol, 2 mmol), 0.3750 g copper sulfate pentahydrate (CuSO4·5H2O, relative molecular weight 281.103 g / mol, 2 mmol), , relative molecular weight of 250g / mol, 1.5mmol), 0.3943g nickel sulfate hexahydrate (NiSO4·6H2O, relative molecular weight of 262.848g / mol, 1.5mmol) and 0.5882g chelating agent sodium citrate (Na3C6H5O7·2H2O, relative molecular weight of 294.10g / mol, 2mmol) were added to 50ml deionized water, stirred to completely dissolve and mix evenly, and the stirring time was 0.5h to obtain a clear and transparent green solution 1;

[0073] B) Weigh 3.9509g potassium ferrocyanide (K3Fe(CN)6, relative molecular mass is 329.2443g / mol, 12mmol) and 0.5882g chelating agent sodium citrate (Na3C6H5O7·2H2O, relative molecular weight is 294.10g / mol, 2mmol) in 50ml deionized water, stir to completely dissolve and mix evenly, stirring time is 0.5h, to obtain a clear and transparent yellow solution II;

[0074] C) Take 100 ml of deionized water, and quickly transfer Solution 1 and Solution 2 to a constant pressure dropping funnel under a nitrogen atmosphere, and use a peristaltic pump to simultaneously drop deionized water at a rate of 20 ml / h to obtain Solution 3, and continue stirring Solution 3 for 3 hours at a speed of 600 rpm;

[0075] D) aging solution 3 at room temperature for 24 hours;

[0076] E) centrifugation, washing with deionized water for 3 times and ethanol for 1 time, each time at 10000 rpm for 5 min, and finally drying in a vacuum oven at 120 °C for 24 h to obtain high entropy, fine particle size, vacancy-rich hexacyanoferrate particles. Example 6

[0077] A) Weigh 0.3345 g of transition metal salts: manganese sulfate monohydrate (MnSO4·H2O, relative molecular weight 223 g / mol, 1.5 mmol), 0.5561 g of ferrous sulfate heptahydrate (FeSO4·7H2O, relative molecular weight 278.05 g / mol, 2 mmol), 0.4217 g of cobalt sulfate heptahydrate (CoSO4·7H2O, relative molecular weight 281.103 g / mol, 1.5 mmol), 0.7500 g of copper sulfate pentahydrate (CuSO4 ·5H2O, relative molecular weight is 250g / mol, total 3mmol), 0.5257g nickel sulfate hexahydrate (NiSO4·6H2O, relative molecular weight is 262.848g / mol, total 2mmol) and 0.5882g chelating agent sodium citrate (Na3C6H5O7·2H2O, relative molecular weight is 294.10g / mol, total 2mmol) are added to 50ml deionized water, stirred to completely dissolve and mix evenly, the stirring time is 1h, and a clear and transparent green solution 1 is obtained;

[0078] B) Weigh 3.9509g potassium ferrocyanide (K3Fe(CN)6, relative molecular mass is 329.2443g / mol, 12mmol) and 0.5882g chelating agent sodium citrate (Na3C6H5O7·2H2O, relative molecular weight is 294.10g / mol, 2mmol) in 50ml deionized water, stir to completely dissolve and mix evenly, stirring time is 0.5h, to obtain a clear and transparent yellow solution II;

[0079] C) Take 100 ml of deionized water, and quickly transfer Solution 1 and Solution 2 to a constant pressure dropping funnel under a nitrogen atmosphere, and use a peristaltic pump to simultaneously drop deionized water at a rate of 20 ml / h to obtain Solution 3, and continue stirring Solution 3 for 3 hours at a speed of 600 rpm;

[0080] D) aging solution 3 at room temperature for 24 hours;

[0081] E) centrifugation, washing with deionized water for 3 times and ethanol for 1 time, each time at 10000 rpm for 5 min, and finally drying in a vacuum oven at 120 °C for 24 h to obtain high entropy, fine particle size, vacancy-rich hexacyanoferrate particles. Example 7

[0082] A) Weigh transition metal salts: 0.4460 g manganese sulfate monohydrate (MnSO4·H2O, relative molecular weight 223 g / mol, 2 mmol), 0.4171 g ferrous sulfate heptahydrate (FeSO4·7H2O, relative molecular weight 278.05 g / mol, 1.5 mmol), 0.5622 g cobalt sulfate heptahydrate (CoSO4·7H2O, relative molecular weight 281.103 g / mol, 2 mmol), 0.3750 g copper sulfate pentahydrate (CuSO4·5 H2O, relative molecular weight of 250g / mol, 1.5mmol), 0.7885g nickel sulfate hexahydrate (NiSO4·6H2O, relative molecular weight of 262.848g / mol, 3mmol) and 0.5882g chelating agent sodium citrate (Na3C6H5O7·2H2O, relative molecular weight of 294.10g / mol, 2mmol) were added to 50ml deionized water, stirred to completely dissolve and mix evenly, and the stirring time was 1h to obtain a clear and transparent green solution 1;

[0083] B) Weigh 3.9509g potassium ferrocyanide (K3Fe(CN)6, relative molecular mass is 329.2443g / mol, 12mmol) and 0.5882g chelating agent sodium citrate (Na3C6H5O7·2H2O, relative molecular weight is 294.10g / mol, 2mmol) in 50ml deionized water, stir to completely dissolve and mix evenly, stirring time is 0.5h, to obtain a clear and transparent yellow solution II;

[0084] C) Take 100 ml of deionized water, and quickly transfer Solution 1 and Solution 2 to a constant pressure dropping funnel under a nitrogen atmosphere, and use a peristaltic pump to simultaneously drop deionized water at a rate of 20 ml / h to obtain Solution 3, and continue stirring Solution 3 for 3 hours at a speed of 600 rpm;

[0085] D) aging solution 3 at room temperature for 24 hours;

[0086] E) centrifugation, washing with deionized water for 3 times and ethanol for 1 time, each time at 10000 rpm for 5 min, and finally drying in a vacuum oven at 120 °C for 24 h to obtain high entropy, fine particle size, vacancy-rich hexacyanoferrate particles.

[0087] Comparative Example 1

[0088] The difference between Comparative Example 1 and Example 1 is that in step A), only 1.9791 g of transition metal ion salt manganese chloride (MnCl2·4H2O, relative molecular weight of 197.91 g / mol, 10 mmol) is added, and the other steps remain the same.

[0089] Take the high entropy, fine particle size, vacancy-rich hexacyanoferrate prepared in Example 1 as an example, as shown in XRD Figure 1 As shown, the XRD of Example 1 and Comparative Example 1 is consistent with the crystal form of Prussian blue compounds, and there is no impurity phase; Example 1 reveals a cubic crystal structure (space group F-43m), with lattice parameters of a = 10.07943 Å, b = 10.07943 Å, c = 10.07943 Å, α = γ = β = 90.00°, according to Figure 2 Inductively coupled plasma mass spectrometry (ICP-OES) and Figure 3 The chemical formulas of high entropy, fine particle size, vacancy-rich hexacyanoferrate and potassium manganese hexacyanoferrate were calculated to be K 0.83 (Mn 0.22 Ni 0.19 Co 0.2 Fe 0.2 Cu 0.19 )[Fe(CN)6] 0.53 1.29 H2O and K 1.36 Mn[Fe(CN)6] 0.88 0.42 H2O, according to the compound configuration entropy calculation formula:

[0090] where n and x i are the tuple fraction and mole fraction of the components, respectively, and R is the universal gas constant. The configurational entropy of Example 1 is 1.61R. The configurational entropy of a single phase exceeding 1.5R proves that Example 1 is a high entropy compound by definition. Figure 4 TEM images show that the side length of each grain is distributed between 15-25nm. Mapping shows that the five elements Fe, Co, Ni, Mn, and Cu are evenly distributed in the agglomerated cubic grains. Electron paramagnetic resonance (EPR) spectroscopy is a test for detecting the unpaired electrons of a material and can be used to study the coordination environment and valence state of the crystal structure. Figure 5 In the EPR diagram, the characteristic peak with g factor = 2.00 is attributed to the symmetrical six-coordinate isolated Fe 3+ Or the characteristic peak of polymerized iron ions. The narrower the peak of the EPR sample, the more Fe 3+ The higher the degree of separation, the more [Fe(CN)6] vacancies are formed in the sample of Example 1, which is consistent with the results of ICP and TG analysis.

[0091] The process of assembling aqueous calcium ion batteries with the hexacyanoferrate prepared in Example 1 is as follows: first, the obtained high entropy, fine particle size, vacancy-rich hexacyanoferrate positive electrode material and the conductive agent-Ketjen black and the binder-PTFE are placed in a mortar in a ratio of 6:3:1 and mixed evenly, then wet-milled for 30 minutes using anhydrous ethanol as a solvent, and finally pressed into sheets using a double-roll mill, and cut into positive electrode sheets of appropriate size after drying, and the loading of active substances is 5-6 mg / cm 2 A three-electrode test device was assembled with a graphite rod electrode with a diameter of 6 mm and a length of 65 mm as the negative electrode, a saturated silver / silver chloride electrode with a diameter of 6 mm as the reference electrode, and 5 M Ca(OTF)2 as the electrolyte.

[0092] The hexacyanoferrate cathode material prepared in Example 1 showed excellent results in the electrochemical performance test after assembling an aqueous calcium ion battery. The test data from the second to the sixth cycle were obtained by cyclic voltammetry (CV) in the range of -0.2 to 1.1 V and at a scan rate of 0.2 mVs−1. Figure 6 As shown. Example 1 shows two pairs of redox peaks, with corresponding voltages of 0.32V / 0.45V and 0.68V / 0.72V, indicating good reversibility in the charge and discharge cycle. In contrast, Comparative Example 1 adds a pair of redox peaks, with voltages of 0.39V / 0.52V, 0.56V / 0.71V and 0.95V / 1.00V, respectively, showing a higher polarization phenomenon. Figure 7 and Figure 8 As shown, in the voltage range of -0.2 to 1.1 V, Example 1 exhibits higher specific capacity and better cycle stability than Comparative Example 1. Specifically, at a current density of 50 mA / g, the specific capacity of Example 1 reaches 111.96 mAh / g and can be stably cycled for 100 cycles. Fig. 9 It is further shown that at different current densities, Example 1 exhibits a higher specific capacity than Comparative Example 1, indicating that its rate performance is more excellent. In addition, after 70 cycles, when the current density is restored to 50 mA / g, the capacity retention rate of Example 1 is close to 100%, while Comparative Example 1 exhibits obvious capacity attenuation and poor cycle stability. Fig.10 As shown, at a current density of 1 A / g, after 5500 cycles, the capacity retention rate of Example 1 still reaches 98.64%, further proving that the high-entropy, fine-particle, vacancy-rich hexacyanoferrate positive electrode material has an excellent long cycle life. Fig.11The results show that Example 1 and Comparative Example 1, as positive electrode materials for aqueous potassium ion batteries, respectively, perform in 3M KCl and 3M KNO3 electrolytes. The results show that Example 1 exhibits high specific capacity and excellent rate performance in both electrolytes, while Comparative Example 1 has almost no specific capacity in 3M KCl electrolyte, indicating that K⁺ may not be effectively embedded and released in Comparative Example 1. Fig.12 As shown, when the high-entropy, fine-particle, vacancy-rich hexacyanoferrate prepared in Example 1 is used as the positive electrode material of an aqueous zinc ion battery, in 3M Zn(OTF)2 and 3M ZnSO4 electrolytes, it also exhibits higher specific capacity and excellent rate performance than the potassium manganese hexacyanoferrate material of Comparative Example 1.

[0093] In summary, the high entropy, fine particle size (15-25nm), vacancy-rich (molar ratio ≥ 30%) hexacyanoferrate cathode material as a cathode material for aqueous metal ion batteries shows high specific capacity, excellent rate performance and excellent cycle stability. It shows a wide range of adaptability in various types of metal ion batteries, indicating that it has great potential in the commercial application of aqueous ion batteries and is a very promising cathode material choice.

[0094] It should be noted that the description of the above technical solutions is exemplary, and this specification can be embodied in different forms and should not be interpreted as being limited to the technical solutions set forth herein. On the contrary, providing these descriptions will make the disclosure of the present invention thorough and complete, and will fully convey the scope disclosed in this specification to those skilled in the art. In addition, the technical solutions of the present invention are limited only by the scope of the claims.

[0095] The various aspects disclosed for describing the present specification and claims are merely examples, and therefore, the present specification and claims are not limited to the details shown. In the above description, when the detailed description of the related known functions or configurations is determined to be unnecessary to obscure the focus of the present specification and claims, the detailed description will be omitted.

[0096] In the case of using “including”, “having” and “comprising” described in the present specification, unless otherwise used, there may also be another part or other parts, and the terms used may generally be in the singular but may also represent the plural form.

[0097] Finally, it should be pointed out that the above content is a further detailed description of the invention in combination with specific implementation methods. It cannot be considered that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, simple replacements made without departing from the concept of the present invention should be regarded as belonging to the protection scope of the present invention. The above embodiments are only more representative examples of the present invention. Obviously, the present invention is not limited to the above embodiments, and there can be many variations. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention should be considered to belong to the protection scope of the present invention.

Claims

1. A method for preparing high entropy fine particle vacancy-rich hexacyanoferrate, characterized in that: High entropy fine particle size vacancy-rich hexacyanoferrate, chemical formula K x M[Fe(CN)6] y ·zH2O, wherein M is a transition metal element, 0.75≤x≤1, 0.4≤y≤0.6, z≤4.0, there are five transition metal elements, the molar mass of each transition metal element accounts for 20% to 30% of all transition metal elements, the molar mass of the vacancy in the ferrocyanide ion accounts for 30% to 50%, the molar mass of the vacancy in the K ion accounts for 30% to 60%, the particle size is 15 to 25 nm, and the preparation method comprises the following steps: A) dissolving the transition metal element salt and the chelating agent in deionized water, stirring to completely dissolve and mix evenly to obtain a clear and transparent solution; B) dissolving potassium ferrocyanide and a chelating agent in deionized water, stirring to completely dissolve and mix evenly to obtain a clear and transparent solution II; C) Under an inert gas atmosphere, solution 1 and solution 2 were quickly transferred to a constant pressure dropping funnel, and were slowly dripped into deionized water using a peristaltic pump while continuously stirring to obtain solution 3; D) aging solution three at room temperature; E) The precipitate was collected by centrifugation, and the obtained product was washed with deionized water and ethanol, and then dried in a vacuum oven.

2. The method for preparing high entropy fine particle vacancy-rich hexacyanoferrate according to claim 1, characterized in that: Transition metal elements include Fe, Co, Ni, Cu and Mn.

3. The method for preparing high entropy fine particle vacancy-rich hexacyanoferrate according to claim 1, characterized in that: The molar masses of transition metal elements are the same.

4. The method for preparing high entropy fine particle vacancy-rich hexacyanoferrate according to claim 1, characterized in that: The anion of the transition metal salt is or 5. The method for preparing high entropy fine particle vacancy-rich hexacyanoferrate according to claim 1, characterized in that: In the step A), the chelating agent is Na3C6H5O7·2H2O, the molar amount of the chelating agent is one fifth of the total molar amount of the transition metal element in the transition metal element salt, and the stirring time is 0.5 to 1 hour. In the step B), the molar amount of the chelating agent is the same as the molar amount of the chelating agent in the step A), the molar amount of potassium ferrocyanide is 6 times the molar amount of the chelating agent, and the stirring time is 0.5 to 1 hour.

6. The method for preparing high entropy fine particle vacancy-rich hexacyanoferrate according to claim 1, characterized in that: In step C), the inert gas is N2, the dripping rate of solution 1 and solution 2 is 15-25 ml / h, and stirring is continued at 600 rpm for 2-3 hours.

7. The method for preparing high entropy fine particle vacancy-rich hexacyanoferrate according to claim 1, characterized in that: In step D), the aging time is 20 to 30 hours. In step E), the product is washed with deionized water 3 times and with ethanol once, each time for 5 minutes, and dried in a vacuum oven at 110 to 150° C. for 20 to 30 hours.

8. An application of high entropy fine particle size vacancy-rich hexacyanoferrate prepared by the method for preparing high entropy fine particle size vacancy-rich hexacyanoferrate as claimed in claim 1, characterized in that: Cathode materials for aqueous metal ion batteries.

Citation Information

Patent Citations

  • High-entropy Prussian blue potassium ion battery positive electrode material, potassium ion battery and preparation method of high-entropy Prussian blue potassium ion battery positive electrode material

    CN115882045A

  • Potassium-based sodium ion battery positive electrode material as well as preparation method and application thereof

    CN116040653A